Antibacterial and antioxidant fibrous silk fibroin-based biological adhesive applied to guided bone regeneration and preparation method of antibacterial and antioxidant fibrous silk fibroin-based biological adhesive
By developing antibacterial and antioxidant fibrous silk fibroin-based bioadhesive agents, the problems of insufficient mechanical properties and infection risks of collagen membranes are solved, and efficient bone regeneration and stable osteogenic environment are achieved.
Patent Information
- Application Number
- CN202411645847.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-21
AI Technical Summary
In the existing guided bone regeneration technology, the mechanical properties of the collagen membrane are insufficient and cannot effectively maintain the bone-forming space, resulting in poor bone regeneration and risk of infection and oxidative stress.
Develop an antibacterial and antioxidant fibrous silk fibrous protein-based bioadhesive agent, mixing fibrous silk fibrous protein with tannin through specific preparation methods to form a highly adhesive, antibacterial and antioxidant bioadhesive agent. Used to mix with bone meal particles to form viscous bone clumps and stabilize the osteogenic environment.
It achieves high bonding strength and compression strength, has good biocompatibility and degradability, can effectively prevent infection and oxidative stress, and promote the regeneration of bone tissue.
Smart Images

Figure CN119488629A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oral medicine, and in particular relates to an antibacterial and antioxidant fibrous silk protein-based bioadhesive used in guided bone regeneration and a preparation method thereof. Background Art
[0002] With the development of oral implant technology and the improvement of people's living standards, implant dentures have become the preferred repair method for patients with edentulous and missing teeth. The most important prerequisite for obtaining and maintaining implant bone integration for a long time is the presence of sufficient healthy bone at the implant site. However, surveys have found that more than half of the implant sites have insufficient bone mass and bone augmentation is necessary, including: block autologous bone transplantation, maxillary sinus floor elevation, alveolar ridge splitting and guided bone regeneration (GBR). (Zhang Fugui, Su Yucheng, Qiu Lixin, et al. Expert consensus on bone augmentation surgery for alveolar bone defects [J]. Prevention and Treatment of Oral Diseases, 2022, 30(04): 229-236.) Among them, GBR has less trauma and a wide range of applications, and is the most widely used bone augmentation technology in implant clinics. The principle of GBR is to place a biological barrier membrane between soft tissue and bone defect, preventing soft tissue cells with faster migration speed from entering the bone defect area, allowing osteoblast precursor cells with slower migration speed to enter the bone defect area first, while protecting blood clots, maintaining the defect gap, and achieving bone regeneration (Ko, YC; Lee, J.; Lee, D.; Seol, YJ; Koo, KT; Lee, YM Progression of experimental peri-implantitis in guided bone regeneration and pristine bone: A preclinical in vivo study. J Periodontol 2023, 94(8), 1032-1044. DOI: 10.1002 / JPER.22-0586 From NLM Medline.; Elgali, I.; Omar, O.; Dahlin, C.; Thomsen, P. Guided bone regeneration: materials and biological mechanisms revisited. Eur J Oral Sci 2017,125(5),315-337.DOI:10.1111 / eos.12364From NLM Medline.).As a representative of absorbable biological barrier membranes, collagen membranes have the advantages of simple operation, degradability, low membrane exposure and infection rate in the surgical area, and are currently the first choice for most GBR surgeries. However, the mechanical properties of collagen membranes are poor and cannot effectively maintain the bone formation space. When the surgical area is subjected to the static pressure of the tissue flap after wound suturing and the dynamic external force generated by the multi-directional functional movement of the oral cavity, the blood clots and granular bone graft materials under the collagen membrane may move slightly or even collapse, seriously interfering with bone regeneration. This has become an important issue affecting the effect of GBR (Li, Q.; He, W.; Li, W.; Luo, S.; Zhou, M.; Wu, D.; Li, Y.; Wu, S. Band-Aid-Like Self-Fixed Barrier Membranes Enable Superior Bone Augmentation. Adv Sci (Weinh) 2023, 10(16), e2206981. DOI: 10.1002 / advs.202206981From NLM Medline.).
[0003] At present, many studies have tried to use titanium mesh with good mechanical properties, tent nails or degradable metal films to form effective support structures to solve the above problems (Kacarevic, ZP; Rider, P.; Elad, A.; Tadic, D.; Rothamel, D.; Sauer, G.; Bornert, F.; Windisch, P.; Hangyasi, DB; Molnar, B.; et al. Biodegradable magnesium fixation screw for barrier membranes used in guided bone regeneration. Bioact Mater 2022, 14, 15-30. DOI: 10.1016 / j.bioactmat.2021.10.036 From NLM PubMed-not-MEDLINE.). However, titanium mesh and tent nails are complicated to operate and require secondary surgery to remove; although degradable metal barrier membranes have been a research hotspot in recent years, their biosafety still needs to be improved. More importantly, these metal materials lack tissue integration and cannot quickly integrate with the soft tissue covering the surface and the blood clots, bone graft materials and bone tissue below. Even if they can form a support, it is difficult to avoid the displacement of blood clots and granular bone graft materials to interfere with bone repair. In order to enhance the stability of the bone regeneration environment, some studies have proposed to tightly wrap the bone graft material with collagen membrane and then fix it with metal membrane nails to limit its movement. However, this technology is highly sensitive and requires secondary surgery to remove the membrane nails, which is difficult to promote and apply. In 2015, Sohn et al. proposed the sticky bone technology, which is to use adhesive substances to stick the bone graft materials together to form bone masses to repair bone defects. This method can reduce the micro-motion between bone implant materials, and the sticky bone mass is easy to operate, showing good potential in maintaining the mechanical stability of the bone regeneration environment. However, the adhesive currently used in stickybone mainly comes from blood extracts (autologous fibrin glue, AFG / concentrated growth factors, CGF). Although it has good biological activity, its adhesion is weak, especially the lack of adhesion to cortical bone. The mechanical properties of the sticky bone mass are not significantly improved. It also requires drawing blood from patients and using special instruments for preparation, which limits its clinical application.However, the biological adhesives currently used in bone defect repair, such as cyanoacrylate and polymethyl methacrylate, have poor biocompatibility and degradability; polymerization heat generation can easily damage surrounding tissues and other defects (Tang, J.; Xi, K.; Chen, H.; Wang, L.; Li, D.; Xu, Y.; Xin, T.; Wu, L.; Zhou, Y.; Bian, J.; et al. Flexible Osteogenic Glue as an All-In-One Solution to Assist Fracture Fixation and Healing. Advanced Functional Materials 2021, 31(38), 2102465. DOI: 10.1002 / adfm.202102465.).
[0004] In clinical practice, surgical intervention may lead to tissue damage and excessive inflammatory response, triggering oxidative stress in the surgical area. Excessive reactive oxygen species (ROS) can inhibit the proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs), induce osteoblast apoptosis, and stimulate the proliferation and activity of osteoclasts. In addition, the oral cavity is a host of multiple microorganisms, and there is a risk of infection after GBR, which seriously hinders bone regeneration. Previous studies have shown that TA has significant antibacterial properties. In addition, TA has been shown to protect endogenous antioxidant enzymes and molecules and act as an antioxidant defense system during hemoperfusion, thus proving that it is effective even in a complex blood environment. Obviously, the development of a bioadhesive with good adhesion, tissue integration, biocompatibility, and antibacterial and antioxidant properties will hopefully solve the bottleneck problem of sticky bone and have important clinical value in promoting the advancement of GBR technology. Summary of the invention
[0005] The purpose of the present invention is to provide an antibacterial and antioxidant fibrous silk protein-based bioadhesive for guided bone regeneration and a preparation method thereof.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing an antibacterial and antioxidant fibrous silk fibroin-based bioadhesive, the method comprising the following steps:
[0008] Step 1, take 2L of 0.01-0.1mol / l Na2CO3 solution and boil it, take 20g of raw silk and add it, keep the temperature constant for 1h, wash it clean, dry the product at 50-70℃ to obtain degummed silk, and store it in a sealed container at room temperature;
[0009] Step 2, add 5 g of degummed silk to 50 ml of 8-10 mol / l LiBr solution and dissolve at 50-70°C for 4 h to form a brown-yellow clear solution;
[0010] Step 3, dialyzing the regenerated silk fibroin solution SF using a 3500 DW dialysis membrane in a deionized water system for 65 to 75 hours; Step 4, removing insoluble matter from the regenerated silk fibroin solution at 10,000 to 25,000 r / min, 10 minutes, and 4° C.;
[0011] Step 5, concentrating the regenerated silk fibroin solution in a 10-20 wt % polyethylene glycol solution system using a 3500 DW dialysis membrane to obtain a 25 wt % fiber-state silk fibroin solution nSF;
[0012] Step 6, prepare 0.1-0.8 g / ml tannic acid solution, mix it with nSF diluted to 5 wt% in a volume ratio of 1:0.1-5 to obtain nSF@TA, let it stand for 30 minutes, freeze-dry and grind it into powder, and store it in a sealed container at 4°C away from light.
[0013] In a specific embodiment, in step 1, the concentration of the Na2CO3 solution is 0.01-0.05 mol / l, such as 0.01-0.03 mol / l, 0.03-0.05 mol / l, more specifically 0.01 mol / l, 0.02 mol / l, 0.03 mol / l, 0.04 mol / l, 0.05 mol / l, etc.
[0014] In a specific embodiment, in step 2, the concentration of the LiBr solution is 8.5-9.5 mol / l, such as 8.5-9.5 mol / l, 8.5 mol / l, 8.8 mol / l, 9.0 mol / l, 9.2 mol / l, 9.3 mol / l, 9.5 mol / l, 9.7 mol / l, 10 mol / l, etc.
[0015] In a specific implementation scheme, in step 4, the centrifugal speed is 15000-20000 r / min, such as 15000 r / min, 18000 r / min, 20000 r / min, etc.
[0016] In a specific embodiment, in step 5, the concentration of the polyethylene glycol solution is 10-20 wt%, such as 10-13 wt%, 13-15 wt%, 14-16 wt%, 15-18 wt%, etc.
[0017] In a specific implementation scheme, in step 6, the concentration of the tannic acid solution is 0.2-0.6 g / ml, such as 0.2 g / ml, 0.3 g / ml, 0.4 g / ml, 0.5 g / ml, 0.6 g / ml, etc.
[0018] In a specific embodiment, in step 6, the tannic acid solution is mixed with nSF diluted to 5 wt % in a volume ratio of 1:0.5 to 2, with specific ratios of 1:0.5, 1:1, 1:1.5, 1:2, etc.
[0019] In a second aspect, the present invention also protects the antibacterial and antioxidant fibrous silk fibroin-based bioadhesive prepared by any of the preparation methods described above.
[0020] In a third aspect, the present invention also protects the use of the antibacterial and antioxidant fibrous silk fibroin-based bioadhesive described above in the preparation of products for guided bone regeneration.
[0021] Mix nSF@TA powder with granular bone powder grafts, add a small amount of physiological saline and stir to form a sticky bone mass. It can tightly integrate the bone surface of the bone defect area, the granular bone powder grafts and the collagen membrane into a whole, while exerting local antibacterial and antioxidant effects, thereby creating a stable bone formation environment and promoting bone tissue regeneration.
[0022] Beneficial Effects
[0023] The nSF@TA powder provided by the invention has high bonding strength, good compression strength, good biocompatibility and good degradability, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the protein secondary structure peak of SF@TA in Example 1.
[0025] Figure 2 This is the protein secondary structure peak of nSF@TA in Example 1.
[0026] Figure 3 This is a semi-quantitative analysis of the protein secondary structure of SF@TA and nSF@TA in Example 1.
[0027] Figure 4 The bonding strength of SF@TA and nSF@TA in Example 1.
[0028] Figure 5 This is the compressive strength of SF@TA and nSF@TA in Example 1.
[0029] Figure 6 This is the degradability of nSF@TA in Example 1.
[0030] Figure 7 The in vivo compatibility of cyanoacrylate with nSF@TA of Example 1.
[0031] Figure 8 The sticky bone block is made of the nSF@TA and bone powder particles in Example 1.
[0032] Fig. 9 The adhesive bone block made of nSF@TA and bone powder particles in Example 1 is bonded to the bone surface.
[0033] Fig.10 The artistic processing of the sticky bone block made of nSF@TA and bone powder particles in Example 1 is "purple rice dumpling". DETAILED DESCRIPTION
[0034] In order to better illustrate the present invention and facilitate understanding of the technical solution of the present invention, the present invention is typical but not restrictive.
[0035] Example 1
[0036] A method for preparing an antibacterial and antioxidant fibrous silk fibroin-based bioadhesive for guided bone regeneration comprises the following steps:
[0037] Step 1, take 2L 0.02mol / l Na2CO3 solution and boil it first, add 20g raw silk into it, keep the temperature constant for 1h, and then wash it thoroughly with deionized water for 5 times. After the moisture of the obtained product is dried at 60℃, the degummed silk is obtained, and it is stored in a sealed and dry place at room temperature.
[0038] Step 2: Add 5 g of degummed silk into 50 ml of 9.3 mol / l LiBr solution and dissolve at 60°C for 4 h to form a brown-yellow clear solution.
[0039] Step 3: Use a 3500 DW dialysis membrane to dialyze in a deionized water system for 72 hours to obtain a regenerated silk fibroin solution (SF).
[0040] Step 4, the regenerated silk fibroin solution is centrifuged at 20000 r / min, 10 min, and 4° C. to remove insoluble matter.
[0041] Step 5, concentrating the regenerated silk fibroin solution in a 15 wt % polyethylene glycol solution system using a 3500 DW dialysis membrane to obtain a 25 wt % fiber-state silk fibroin solution (nSF), which can be further diluted as needed.
[0042] Step 6, prepare a 0.4 g / ml tannic acid solution, mix it with nSF diluted to 5 wt % in a volume ratio of 1:1 to obtain nSF@TA, let it stand for 30 minutes, freeze-dry and grind it into powder, and store it in a sealed container at 4°C away from light.
[0043] Example 2
[0044] A method for preparing an antibacterial and antioxidant fibrous silk fibroin-based bioadhesive for guided bone regeneration comprises the following steps:
[0045] Step 1, take 1L 0.01mol / l Na2CO3 solution and boil it first, add 20g raw silk into it, keep the temperature constant for 1h, and then wash it thoroughly with deionized water for 5 times. After the moisture of the obtained product is dried at 60℃, the degummed silk is obtained, and it is stored in a sealed and dry place at room temperature.
[0046] Step 2: Add 5 g of degummed silk to 50 ml of 8.5 mol / l LiBr solution and dissolve at 50 °C for 4 h to form a brown-yellow clear solution.
[0047] Step 3: Use a 3500 DW dialysis membrane to dialyze in a deionized water system for 65 hours to obtain a regenerated silk fibroin solution (SF).
[0048] Step 4, the regenerated silk fibroin solution is centrifuged at 10000 r / min, 10 min, and 4° C. to remove insoluble matter.
[0049] Step 5, concentrating the regenerated silk fibroin solution in a 10 wt % polyethylene glycol solution system using a 3500 DW dialysis membrane to obtain a 25 wt % fiber-state silk fibroin solution (nSF), which can be further diluted as needed.
[0050] Step 6, prepare a 0.2 g / ml tannic acid solution, mix it with nSF diluted to 5 wt % in a volume ratio of 1:2 to obtain nSF@TA, let it stand for 30 minutes, freeze-dry and grind it into powder, and store it in a sealed container at 4°C away from light.
[0051] Example 3
[0052] A method for preparing an antibacterial and antioxidant fibrous silk fibroin-based bioadhesive for guided bone regeneration comprises the following steps:
[0053] Step 1, take 2L 0.05mol / l Na2CO3 solution and boil it first, add 20g raw silk into it, keep the temperature constant for 1h, and then wash it thoroughly with deionized water for 5 times. After the moisture of the obtained product is dried at 60℃, the degummed silk is obtained, and it is stored in a sealed and dry place at room temperature.
[0054] Step 2: Add 5 g of degummed silk into 50 ml of 10 mol / l LiBr solution and dissolve at 70 °C for 4 h to form a brown-yellow clear solution.
[0055] Step 3: Use a 3500 DW dialysis membrane to dialyze in a deionized water system for 75 hours to obtain a regenerated silk fibroin solution (SF).
[0056] Step 4, the regenerated silk fibroin solution is centrifuged at 25000 r / min, 10 min, and 4° C. to remove insoluble matter.
[0057] Step 5, concentrating the regenerated silk fibroin solution in a 20 wt % polyethylene glycol solution system using a 3500 DW dialysis membrane to obtain a 25 wt % fiber-state silk fibroin solution (nSF), which can be further diluted as needed.
[0058] Step 6, prepare a 0.6 g / ml tannic acid solution, mix it with nSF diluted to 5 wt % in a volume ratio of 1:0.5 to obtain nSF@TA, let it stand for 30 minutes, freeze-dry and grind it into powder, and store it in a sealed container at 4°C away from light.
[0059] Performance Testing
[0060] 1. Protein structure analysis
[0061] The SF@TA obtained in Example 1 was subjected to protein secondary structure peak analysis, as shown in FIG. Figure 1 As shown in FIG. 1 , the secondary structure composition ratio of SF@TA protein is analyzed by performing protein secondary structure peak separation on nSF@TA obtained in Example 1. Figure 2 The ratio of the secondary structure of nSF@TA protein is shown in Figure 2. SF@TA and nSF@TA were analyzed by Fourier transform infrared spectroscopy (FTIR, Thermo Scientific Nicolet iS10, USA) at a resolution of 4 cm -1 In the case of 500 to 4000 cm -1 The amide-I band (1600-1700cm -1 ) were calibrated and analyzed to determine the content of α-helix and β-sheet structures.
[0062] Figure 3 The semi-quantitative analysis of the protein secondary structure of SF@TA and nSF@TA in Example 1 was repeated 3 times and statistical analysis was performed. Figure 3 As shown, the β-sheet content of nSF@TA is significantly higher than that of SF@TA, thereby enhancing the intermolecular forces.
[0063] 2. Bond strength comparison
[0064] The bonding strength of SF@TA and nSF@TA obtained in Example 1 was compared: 30×20×10 mm bone blocks were cut from pig femurs. Before testing, the bone blocks were pretreated in PBS solution at 37°C for 30 min, and SF@TA / nSF@TA was applied to the bonding surface of the bone blocks (30×20 mm). The bonding strength was evaluated using a universal material testing machine (Instron R3655, USA) to determine the maximum stress that would break the bond. The results are shown in Figure 2. Figure 4 As shown, when the TA concentration is 0.4 g / ml, the bonding strength of nSF@TA is significantly higher than that of SF@TA.
[0065] Comparison of the compression strength of SF@TA and nSF@TA obtained in Example 1: SF@TA / nSF@TA was made into a cube (1cm×1cm×1cm). The compression modulus was evaluated using a universal material testing machine (Instron R3655, USA). Figure 5 It can be seen that when the TA concentration is 0.4 g / ml, the compressive strength of nSF@TA is significantly higher than that of SF@TA.
[0066] 3. Degradability test
[0067] The degradability of nSF@TA obtained in Example 1 was analyzed:
[0068] (1) In vitro experiment: 100 mg (dry weight) of nSF@TA fine powder sample was converted into hydrogel at 37°C, 200 rpm, PBS (changed every three days), and then immersed for 28 days. At the 3rd, 5th, 7th, 14th, 21st and 28th day, freeze-dried and weighed. The degradation rate was calculated using the following formula. Wx: residual dry weight;
[0069] (2) In vivo experiment: 100 mg (dry weight) of nSF@TA samples were implanted into the subcutaneous tissue of SD rats. On days 7, 14, and 28, the animals were sacrificed, and the nSF@TA samples were carefully removed, the surrounding tissues were removed, and then further freeze-dried for weighing. The in vivo degradation rate was calculated using the following formula. Wx: residual dry weight.
[0070] The results are as follows Figure 6 It can be seen that nSF@TA underwent significant degradation both in vitro and in vivo within 27 days.
[0071] 4. Biocompatibility testing
[0072] The in vivo compatibility of nSF@TA obtained in Example 1 was compared with that of cyanoacrylate: A total of 12 SD male rats were used to evaluate the biocompatibility of nSF@TA in vivo. For each rat, a skin incision (10 mm in length) was made on both sides of its back, and then 100 mg of nSF@TA and 100 mg of cyanoacrylate produced by Guangzhou Baiyun Medical Adhesives Co., Ltd. (both sterilized) were implanted on both sides. Tissues were removed from the surrounding tissues of the 2-week and 4-week samples, fixed with 4% paraformaldehyde for 48 hours, and then dehydrated with alcohol in turn. The tissue specimens were embedded in paraffin and cut into 4-micron thick sections. The sections were stained with HE and immunohistochemistry for CD68.
[0073] The results are as follows Figure 7 As shown, both HE and CD68 staining indicated that the degree of inflammation of nSF@TA was significantly lower than that of cyanoacrylate.
[0074] 5. Adhesive Bone Block Test
[0075] The nSF@TA obtained in Example 1 and bone powder particles were made into sticky bone blocks. Figure 8 As shown, nSF@TA can integrate and bond bone powder particles well. Fig. 9 The adhesive bone block made of nSF@TA and bone powder particles is bonded to the bone surface. Fig. 9 It can be seen that adhesive bone can integrate and bond well to the cortical bone surface. Fig.10 The artistic processing of sticky bone blocks made of nSF@TA and bone powder particles into "purple dumplings" Fig.10 It can be seen that viscoelastic bone has good morphological plasticity.
[0076] The protection content of the present invention is not limited to the above embodiments. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention and are protected by the attached claims.
Claims
1. A method for preparing an antibacterial and antioxidant fibrous silk fibroin-based bioadhesive, characterized in that: The method comprises the following steps: Step 1: Take 2L of 0.01~0.1mol / l Na2CO3 solution and boil it, then add 20g of raw silk. Keep the temperature constant for 1 hour, wash and dry the product at 50-70℃ to obtain degummed silk, and store it in a sealed container at room temperature; Step 2, add 5 g of degummed silk to 50 ml of 8-10 mol / l LiBr solution and dissolve at 50-70 °C for 4 h to form a brown-yellow clear solution; Step 3, dialyzing in a deionized water system for 65-75 hours using a 3500 DW dialysis membrane to obtain a regenerated silk fibroin solution SF; Step 4, the regenerated silk fibroin solution is centrifuged at 10000-25000 r / min for 10 min at 4° C. to remove insoluble matter; Step 5, concentrating the regenerated silk fibroin solution in a 10-20 wt % polyethylene glycol solution system using a 3500 DW dialysis membrane to obtain a 25 wt % fiber-state silk fibroin solution nSF; Step 6, prepare 0.1-0.8 g / ml tannic acid solution, mix it with nSF diluted to 5 wt% in a volume ratio of 1:0.1-5 to obtain nSF@TA, let it stand for 30 min, freeze-dry and grind it into powder, and store it in a sealed container at 4°C away from light.
2. The method for preparing the antibacterial and antioxidant fibrous silk fibroin-based bioadhesive according to claim 1, characterized in that: In the step 1, the concentration of the Na2CO3 solution is 0.01-0.05 mol / l.
3. The method for preparing the antibacterial and antioxidant fibrous silk fibroin-based bioadhesive according to claim 1, characterized in that: In step 2, the concentration of the LiBr solution is 8.5-10 mol / l.
4. The method for preparing the antibacterial and antioxidant fibrous silk fibroin-based bioadhesive according to claim 1, characterized in that: In step 4, the centrifugal speed is 10000~25000r / min.
5. The method for preparing the antibacterial and antioxidant fibrous silk fibroin-based bioadhesive according to claim 1, characterized in that: In step 5, the concentration of the polyethylene glycol solution is 10-20 wt %.
6. The method for preparing the antibacterial and antioxidant fibrous silk fibroin-based bioadhesive according to claim 1, characterized in that: In step 6, the concentration of the tannic acid solution is 0.2-0.6 g / ml.
7. The method for preparing the antibacterial and antioxidant fibrous silk fibroin-based bioadhesive according to claim 1, characterized in that: In the step 6, the tannic acid solution and the nSF diluted to 5 wt % are mixed in a volume ratio of 1:0.5-2.
8. The antibacterial and antioxidant fibrous silk fibroin-based bioadhesive according to any one of claims 1 to 7.
9. Use of the antibacterial and antioxidant fibrous silk protein-based bioadhesive according to claim 8 in the preparation of products for guided bone regeneration.